Deteksi Ketinggian Air Pada Citra Screenshot Dengan Menerapkan Metode Template Matching - Purwati, Rima (Bulletin of Data Science, 2023)
The current development of digital technology significantly impacts our daily lives. One prominent change is the digitization of image data, altering how we interact with the world around us. Digital technology enables digital media users to utilize image processing as an intelligent solution to tackle various challenges. A critical aspect of this technological application pertains to water level detection, particularly relevant in household water storage. Water storage serves as a pivotal element in storing clean water reserves to meet daily needs. Ensuring an adequate and high-quality water supply within these storage systems is a top priority. However, difficulties arise when attempting to monitor water levels, especially at night when illumination is minimal. To overcome this obstacle, innovative techniques for water detection and recognition are employed to accurately measure water levels during nighttime, aided by easily deployable IP camera technology. One efficient method involves template matching techniques. This innovation serves as a tangible example of how technological advancements, particularly in image processing, can bring about positive changes in managing and monitoring water availability in a household context. Consequently, technology plays a crucial role in meeting daily water needs more effectively, ensuring an ample water supply within the household environment.